اليات التخارج الاخلاقي الشائعة لدى طلبة الجامعة (Journal of Imam Al-Kadhim College, 2023)
The concept of moral externalization refers to the tendency of individuals to use cognitive means that disrupt organizing processes Moral self and causes individuals to make unethical decisions most of the time without any sense of guilt to provide excuses to commit immoral acts, and individuals use moral exclusion in order to get rid of conflict and anxiety and stress caused by the harmful act.